Салтово-маяцький кремаційний могильник "Государів Яр" у Середньму Подонців’ї - Голубєв, А.М. (Археологія, 2017)
До наукового обігу вводиться салтово-маяцький могильник з поховальними комплексами за обрядом кремації. Presented to the scientific circles is an information on Hosudariv Yar, a site of Saltiv-Maiaky culture, as on a burial ground with cremations discovered in the Donets River middle region in Slaviansk Region of Donetsk Oblast. The archaeological prospecting in 2015 field season showed that the burial ground is deeply destroyed by the World War II operations and by the modern treasure-hunters. A burial with cremation and a cache were discovered in trenches 1 and 2 correspondingly. Materials found there have wide analogies in cremation assemblages from both the region, and outside. Peculiar for all cremation assemblages of the Donets River middle region is a presence in burials and caches of in fact the whole set of tools for tillage and harvesting, as well as almost the whole diversity of craft tools of the culture with a minimal presence of arms. This fact, to the authors’ opinion, can testify not for the ethnically diverse structure of the population, namely, the bearers of cremation custom from the Donets River upper and middle flow regions, but for its social and probably tribal division into two wings: «white» and «black». В научный оборот вводится информация о памятнике салтово-маяцкой культуры «Государев Яр» как о кремационном могильнике, который выявлен в Среднем Подонцовье в Славянском р-не Донецкой обл. Разведками полевого сезона 2015 г. установлено, что могильник сильно разрушен боевыми действиями времен Второй мировой войны и современными кладоискателями. В шурфах 1 и 2 могильника выявлены кремационное погребение и тайник соответственно. Материалы из них находят широкие аналогии в кремационных комплексах как региона, так и за его пределами. Особенностью всех кремационных комплексов Среднего Подонцовья является наличие в погребениях и тайниках практически полного набора орудий труда для обработки земли и сбора урожая, а также практически всех разновидностей ремесленных инструментов культуры при минимальном присутствии вооружения. Этот факт, по нашему мнению, может свидетельствовать не о разноэтничном составе населения — носителей обряда кремации Верхнего и Среднего течения Донца, а о его социальном и, возможно, племенном делении на два крыла — «белых» и «черных».